Whitener pain - characteristic and fracture - Siminska, Joanna; Nowacka, Krystyna; Grzyb, Sebastian; Szostak, Mateusz; Hagner-Derengowska, Magdalena; Hagner, Wojciech (Journal of Education, Health and Sport, 2019)
Back pain can be dull dull character, which most often are located only in the lumbar area, in the case where there was not a disagreement radicular -vertebral, or may radiate to the lower limbs, depending on the level and degree of compression of the spinal roots. With a high degree of changes occurring that contribute to the emergence of a significant narrowing of the intervertebral holes and as a result the pressure on the roots, sensory and motor symptoms depend on the level and degree of oppression. It should, however, take into account that even large osteophytes on the anterior-lateral edges of the vertebral bodies, which do not give the roots of oppression, may be clinically silent almost symptomatically. Proper diagnosis, determine the type of pain as well as to diagnose the cause of the pain is important in the further process of rehabilitation.